Prevalence and factors associated with telogen effluvium in adult females at Makkah region, Saudi Arabia: A retrospective study - M.I. Fatani; A.M. Bin mahfoz; A.H. Mahdi; K.A. Alafif; W.A. Hussain; A.S. Khan; A.A. Banjar (Wolters Kluwer Medknow Publications, 2015)
Background: Data on the epidemiology of telogen effluvium (TE) are limited, and its true incidence is largely unknown. Our aim is to calculate the prevalence of TE and evaluate its comorbidities and its relation to iron-deficiency anemia. Methods: We performed a retrospective review of 279 medical records of the patients with TE seen at Hera Hospital, Makkah, Saudi Arabia, between 2011 and 2013. Results: Of 279 female patients (mean age: 29.82 years), 58.5% of the patients were between the age of 21 and 40. Hypothyroidism was reported in 21.1% of the patients, dermatitis in 11.8%, diabetes mellitus in 5.7%, and bronchial asthma in 3.6%. Low hemoglobin was observed in 94.9% of the patients, low MCH in 99.6%, and low hematocrit in 90.21%. Serum ferritin was at ⩽30 ng/mL in 64% of the patients and ⩽70 ng/mL in 89.1%. The systemic treatment included the following: iron supplementation in 58.8%, folic acid in 51.3%, and zinc in 25.1%. Topical treatments included steroid in 63.1%, minoxidil in 34.8%, hair tonic in 68.8%, and antidandruff in 19.4%. Conclusions: All patients were females, with most of their ages of onset between 21 and 40. It was commonly associated with iron-deficiency anemia and hypothyroidism.